Examining the impact of MnO2 and CeO2 on mechanical properties, degradability, and the microstructure of Zirconia - Dinesh R.; Meenaloshini S.; Mohsen G.; Sankar U. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The effect of CeO2 and MnO2 additions (up to 1 wt%) on the sintering behaviour of yttria-stabilized zirconia sintered from 1250C to 1450C was investigated. From the findings, mechanical properties are likely to improve via the addition of 0.2 wt% CeO2 and 0.8 wt% MnO2 with Y-TZP. This composition increased the density of Y-TZP. The value of density achieved was about 6.04 g/cm3, approximately 98% of the theoretical density of Y-TZP. The mechanical properties (i.e. hardness and strength) of the material were significantly increased as well. Besides that, the 0.2 wt% CeO2 and 0.8 wt% MnO2 composite displayed higher elasticity of 211 GPa compared to pure Y-TZP with a theoretical value of 200 GPa. Sintering over 1450 C is expected to degenerate the composites physical and mechanical properties. Sintering at higher temperatures (>1350 C) would affect the properties of the composite, due to a bigger grain size obtained at high temperature. BEIESP.